2019
DOI: 10.1111/jcal.12413
|View full text |Cite
|
Sign up to set email alerts
|

21st‐century competences: The relation of ICT competences with higher‐order thinking capacities and teamwork competences in university students

Abstract: The Knowledge Society, along with the non‐stop growing technological evolution, entails university students acquiring new competences for them to be successful in society. These are called 21st‐century competences that come as high‐skill competences – higher‐order thinking capacities and teamwork competences – and information and communication technologies (ICT) competences – technological, pedagogical and ethical. This study aims to determine the link between ICT competences and high‐skill competences. A corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 31 publications
3
20
0
1
Order By: Relevance
“…This indicates that the analysis of this competence is necessary, because its low dominance has repercussions in a lower and unqualified educational use of ICT by the teacher [ 21 ]. On the other hand, as its mastery has a transversal impact on other competences that the teacher must have, its study and analysis, it becomes more necessary [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the analysis of this competence is necessary, because its low dominance has repercussions in a lower and unqualified educational use of ICT by the teacher [ 21 ]. On the other hand, as its mastery has a transversal impact on other competences that the teacher must have, its study and analysis, it becomes more necessary [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The TWC-CQ scale also provided "characteristics" for "effective teams" in culturally diverse settings according to Navarro et al's (2017) [16] opinion. Finally, the information and communication contents in the TWC-CQ scale echoed with Almerich et al's (2020) [17] call to accumulate 21st-century competencies. In addition, the TWC-CQ scale covered abilities, such as high levels of specialist knowledge, rapid responses, and adaptability, which Nadal et al (2015) [15] emphasized.…”
Section: Contribution To the Twc Assessment Theorymentioning
confidence: 93%
“…Nowadays, in academic settings, teachers' perceptions are not the only source of assessment, but also consider other agents involved in teamwork, such as the students themselves through peer ratings and self-evaluations [14]. Teamwork competence in higher education settings was highly valued based on the knowledge from team science, and the characteristics of effective teams of students were gradually generated [16], and it is positively related to 21st-century competence (information and communication technologies) [17].…”
Section: Assessment Of Teamwork Competencementioning
confidence: 99%
“…In some jobs, basic ICT skills are not specific to the profession; however, many job profiles in engineering industries increasingly require engineers with good technical expertise [ 6 ] and high-level ICT-Work and cross-functional skill capabilities [ 7 ] to apply specific software in their profession [ 8 ]. Merely possessing basic ICT skills is not sufficient because the labor market in the digital age and in the critical COVID-19 situation requires more technology capabilities and high-skill competencies [ 9 ]. Therefore, engineering students need to have sufficient knowledge and skills in using complex ICT systems for their profession in the labor market and for career development.…”
Section: Introductionmentioning
confidence: 99%
“…ICT competencies are essential to students in any career field, especially for engineering students, whose subject matter is difficult to study. Studies have reported that ICT competencies in curricula would benefit learning in terms of both cognitive and noncognitive development [ 10 , 11 ], for example, increased higher-order thinking capacities [ 9 , 12 ], self-efficacy [ 13 ], learning processes [ 14 ], academic performance [ 13 , 15 ], and facilitating the development of students’ work skills [ 16 ]. In contrast, a study by Meng, et al [ 17 ] found a significantly negative association between perceived ICT competencies and student achievement in China.…”
Section: Introductionmentioning
confidence: 99%